A short form of the neonatal intensive care unit family needs inventory - Elisabete Alves; Milton Severo; Mariana Amorim; Catarina Grande; Susana Silva (Elsevier, 2016)
Objective: The identification of parental needs in Neonatal Intensive Care Units is essential to design and implement family-centered care. This article aims to validate the Neonatal Intensive Care Units Family Needs Inventory for the Portuguese population, and to propose a Short Form. Methods: A linguistic adaptation of the Neonatal Intensive Care Units Family Needs Inventory, a self-report scale with 56-items, was performed. The instrument was administered to 211 parents of infants hospitalized in all level III Neonatal Intensive Care Units in the North of Portugal, 15-22 days after admission (July of 2013-June of 2014). The number of items needed to achieve reliability close to 0.8 was calculated using by the Spearman-Brown formula. The global goodness of fit of the scale was evaluated using the comparative fit index. Construct validity was assessed through association of each dimension score with socio-demographic and obstetric characteristics. Results: Exploratory factor analysis revealed two dimensions, one focused on parents' needs and another on the infant's needs. To compose the Short Form Inventory, items with ceiling effect were eliminated and 22 items were submitted to confirmatory analysis, which supported the existence of two dimensions (CFI = 0.925). The Short Form showed a high degree of reliability (alpha ≥ 0.76). Less educated and older parents more frequently attributed a significantly higher importance to parent-centered needs, while parents of multiples revealed a tendency to value infant-centered needs. Conclusions: The Short Form of the Neonatal Intensive Care Units Family Needs Inventory is a brief, simple, and valid instrument with a high degree of reliability. Further studies are needed to explore associations with practices of family-centered care. Resumo: Objetivo: A identificação de necessidades parentais em Unidades de Cuidados Intensivos Neonatais (UCINs) é essencial para planejar e implementar cuidados centrados na família. Este artigo pretende validar o Inventário de Necessidades da Família em UCIN na população portuguesa e propor uma Versão Curta do mesmo. Metodologia: Foi realizada uma adaptação linguística do Inventário de Necessidades da Família na UCIN, uma escala de autorrelato com 56 itens. O instrumento foi aplicado a 211 pais de bebês internados em todas as UCINs de nível III no Norte de Portugal 15 a 22 dias após a internação (julho de 2013-junho de 2014). O número de itens necessários para atingir uma confiabilidade próxima a 0,8 foi calculado pela fórmula de Spearman-Brown. A adequação global da escala foi avaliada pelo índice de ajuste comparativo (CFI). A validade de construto foi avaliada através da associação do escore de cada dimensão com características sociodemográficas e obstétricas. Resultados: A análise fatorial exploratória revelou duas dimensões, uma focada nas necessidades dos pais e outra, nas necessidades do bebê. Para compor a Versão Curta do Inventário, os itens com efeito teto foram eliminados, e 22 itens foram submetidos a análise confirmatória, que sustentou a existência de duas dimensões (CFI = 0,925). A Versão Curta apresentou alto grau de confiabilidade (alfa ≥ 0,76). Pais mais velhos e com menor escolaridade atribuíram, mais frequentemente, maior importância à subescala de necessidades centradas nos pais enquanto os pais de gêmeos revelaram uma tendência de valorizar as necessidades centradas nos bebês. Conclusões: A Versão Curta do Inventário de Necessidades da Família em UCIN é um instrumento breve, simples e válido com alto grau de confiabilidade. São necessários estudos adicionais para explorar as associações com práticas de cuidados centrados na família. Keywords: Neonatal intensive care units, Needs assessment, Parents, Validation studies as topic, Palavras-chave: Unidade de Cuidados Intensivos Neonatais, Avaliação de necessidades, Pais, Estudos de validação como assunto